2012
DOI: 10.1007/s11540-012-9217-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fusarium spp. Causing Potato Dry Rot in China and Susceptibility Evaluation of Chinese Potato Germplasm to the Pathogen

Abstract: Dry rot is a serious potato disease and causes significant losses in China. Research efforts on potato dry rot have been very limited as well as the attempts to characterize the pathogen in the major potato production regions of China. A total of 260 Fusarium isolates were identified in 698 potato tubers collected in six important potato production regions of northern China, out of which five different Fusarium species, Fusarium sambucinum, F. avenaceum, F. oxysporum, F. equiseti, and F. acuminatum, were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 20 publications
4
46
1
2
Order By: Relevance
“…These isolates might be secondary pathogens or might require specific environmental factors that were not reproduced in the laboratory to cause infection. Less abundant but definitely pathogenic were F. sambucinum, F. avenaceum, F. culmorum and F. graminearum, and these results are in accordance with those of earlier reports (Peters et al 2008b;Du et al 2012). In our study, statistical analysis performed on the four of pathogenic Fusarium spp.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These isolates might be secondary pathogens or might require specific environmental factors that were not reproduced in the laboratory to cause infection. Less abundant but definitely pathogenic were F. sambucinum, F. avenaceum, F. culmorum and F. graminearum, and these results are in accordance with those of earlier reports (Peters et al 2008b;Du et al 2012). In our study, statistical analysis performed on the four of pathogenic Fusarium spp.…”
Section: Discussionsupporting
confidence: 93%
“…1). The resulting phylogenetic relationships remained in agreement with previous studies (Du et al 2012;Kristensen et al 2005;Zhang et al 2006). The isolates of the same species were grouped together in the resulting MP tree, supporting their correct identification.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Kristensen et al (2005) emphasize the importance of the TEF-1α phylogenetic analysis because they have concluded that this is able to identify species of monophyletic Fusarium. According to Du et al (2012), the region TEF-1α was efficient in the classification, into four distinct groups of species, when they sequenced 41 isolates of Fusarium since the similarity indices were higher than 95%. Hsuan et al (2011) were successful in the identification of isolates of Fusarium sp., belonging to the complex Gibberella fujikuroi obtained from maize (Zea mays), rice (Oryza sativa) and sugarcane (Saccharum officinarum) in Malaysia.…”
Section: Discussionmentioning
confidence: 99%
“…A new molecular method of PCR is widely used in science experiments together with traditional morphological and physiological research methods of Fusarium spp. [9,10].…”
Section: Introductionmentioning
confidence: 99%